PENGARUH PERSEPSI NASABAH DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH DALAM MENGGUNAKAN M-BANKING (STUDI KASUS PADAMAHASISWA JURUSAN PERBANKAN SYARIAH ANGKATAN 2019 UNIVERSITAS ISLAM NEGERI SJECH M. DJAMIL DJAMBEK BUKITTINGGI) - Cynthia Suci Hati Faisal; Amsah Hendri Doni (BORJUIS: JURNAL OF ECONOMY, 2024)
The use of internet media among students studying Sharia Banking at the Sjech M. Djamil Djambek Bukittinggi State Islamic University has grown rapidly. However, the perception of students as bank customers is still lacking due to their limited knowledge regarding how to use m-banking and the lack of quality of service provided to customers. This research aims to determine the influence of customer perceptions and service quality on customer satisfaction in using m-banking. The research method used is quantitative, with data collection through observation and questionnaires. Data analysis techniques include correlation analysis, multiple linear regression analysis, t test and determinant test. The results show that there is a significant influence of customer perception and service quality on customer satisfaction, with a strong correlation and a large contribution.